The Breastfeeding Implementation in the Primary Health Center : A Case Study at Puskesmas Tutuyan Working Area, East Bolaang Mongondow Regency, Indonesia - Radjamuda, Nelawati; Astuti, Dhesi Ari; Kartini, Farida (Buletin Ilmu Kebidanan dan Keperawatan, 2024)
Breastfeeding provides optimal nutrition for infants and is a key global public health strategy for improving children's health. However, a low understanding of breastfeeding among mothers, families, and communities poses challenges. This study explored breastfeeding practices in Puskesmas Tutuyan, East Bolaang Mongondow Regency. Using a qualitative phenomenological design, six mothers with infants aged 0-6 months and two midwives were interviewed and observed. Data were analyzed using Collaizi's 1987 seven-step method. Findings showed that while mothers aged 23-35 understood the benefits of breastfeeding, their attitudes and practices were lacking, often citing insufficient breast milk and inadequate support from health workers. Three factors influenced breastfeeding practices: predisposing (knowledge and attitudes), reinforcing (milk supply and information availability), and enabling (support from health workers and family). It is recommended that midwives increase educational efforts, provide breastfeeding support, and establish support groups, with regular monitoring and evaluation every six months to improve breastfeeding practices in Puskesmas Tutuyan.